Assessment of F₅ Mungbean Genotypes from Intergeneric Hybridization with Common Bean for Agronomic Performance, Heritability, Variance Components, and Genetic Uniformity - Binti Nur Aisah; Aprilia Tiara Ikhwani; Agus Budi Setiawan; Aziz Purwantoro; Dyah Weny Respatie; Erlina Ambarwati; Listy Anggraeni; Chee How Teo; Chandra Setyawan; Aniswatul Khamidah (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Genetic improvement in mungbean (Vigna radiata L. [Wilczek]) is constrained by its narrow genetic base. Introducing genetic material from common bean (Phaseolus vulgaris L.) through intergeneric hybridization offers a promising strategy for enhancing yield potential and advancing sustainable agriculture. However, limited studies have evaluated the agronomic performance and genetic parameters of progenies derived from such crosses. This study aimed to assess agronomic performance, estimate genetic parameters, and evaluate genetic uniformity in mungbean progenies, to identify superior lines for breeding programs. The field experiment was conducted using a randomized complete block design with four replicates. Five selected F₅ genotypes (C419, B423, B1922, B119, and B1124), along with the mungbean progenitor PKHPL-1, were evaluated. Traits assessed included vegetative, generative, and yield-related characteristics. Significant variation was observed among genotypes for yield-related traits, while plant height, number of flowers, and phenological traits showed relative uniformity. Genotype C419 exhibited the highest agronomic performance, with superior values in 100-seed weight, number of seeds per pod, seed weight per plant, and number of pods per plant. High heritability was recorded for pod length and 100-seed weight (90.63% and 90.32%, respectively), indicating strong genetic control and potential for effective selection. Principal component analysis confirmed the major contribution of these traits to yield variation. Furthermore, molecular analysis using IRAP markers revealed high genetic uniformity in genotype C419. These findings demonstrate the potential of intergeneric hybridization for enhancing yield-related traits in mungbean and identify genotype C419 as a promising line for future breeding efforts.